HmsC Controls Yersinia pestis Biofilm Formation in Response to Redox Environment - Ren, Gai-Xian; Guo, Xiao-Peng; Sun, Yi-Cheng (Frontiers in Cellular and Infection Microbiology, 2017)
Yersinia pestis bioﬁlm formation, controlled by intracellular levels of the second messenger molecule cyclic diguanylate (c-di-GMP), is important for blockage-dependent plague transmission from fleas to mammals. HmsCDE is a tripartite signalling system that modulates intracellular c-di-GMP levels to regulate biofilm formation in Y. pestis. Previously, we found that Y. pestis biofilm formation is stimulated in reducing environments in an hmsCDE-dependent manner. However, the mechanism by which HmsCDE senses the redox state remains elusive. Using a dsbA mutant and the addition of Cu2+ to simulate reducing and oxidising periplasmic environments, we found that HmsC protein levels are decreased and the HmsC-HmsD protein-protein interaction is weakened in a reducing environment. In addition, we revealed that intraprotein disulphide bonds are critical for HmsC since breakage lowers protein stability and diminishes the interaction with HmsD. Our results suggest that HmsC might play a major role in sensing the environmental changes.